2015
DOI: 10.1177/1087054715573992
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Self-Reported ADD/ADHD in a Large National Sample of Canadian Adults

Abstract: In a national sample of Canadian adults, self-reported ADD/ADHD was associated with significant psychiatric comorbidity. Gender differences were also noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
60
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 52 publications
7
60
2
Order By: Relevance
“…However, the prevalence rates of depression among children diagnosed with ADHD differ greatly between studies due to methodological variety and heterogeneous samples. In recent years, cross-sectional studies have shown that the depression rates in youths with ADHD range from 9.3% to 40.7% (Biederman et al, 2008a;Di Trani et al, 2014;Hesson and Fowler, 2015;Roy et al, 2014;Yuce et al, 2013). Meanwhile, longitudinal studies have reported that developing depression in ADHD sufferers occurs at a rate of 5.4-8.9% (Chen et al, 2013;Jerrell et al, 2015;Klein et al, 2012;McIntyre et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, the prevalence rates of depression among children diagnosed with ADHD differ greatly between studies due to methodological variety and heterogeneous samples. In recent years, cross-sectional studies have shown that the depression rates in youths with ADHD range from 9.3% to 40.7% (Biederman et al, 2008a;Di Trani et al, 2014;Hesson and Fowler, 2015;Roy et al, 2014;Yuce et al, 2013). Meanwhile, longitudinal studies have reported that developing depression in ADHD sufferers occurs at a rate of 5.4-8.9% (Chen et al, 2013;Jerrell et al, 2015;Klein et al, 2012;McIntyre et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Their persistence has been associated with functional impairment in psychosocial, educational, professional and family functioning ( Biederman, Petty, Woodworth et al, 2012 ). In addition, compared to adults without ADHD, adults with ADHD experience higher levels of anxiety disorders, mood disorders, conduct disorders and antisocial personality disorder ( Hesson and Fowler, 2015 , Miranda et al, 2014 , Nogueira et al, 2014 ), as well as an increased risk of abuse/dependence on nicotine, alcohol, marijuana, cocaine, and other unspecified substances ( Breyer et al, 2014 , van Emmerik-van Oortmerssen et al, 2012 ). Of the core ADHD symptoms, hyperactivity/impulsivity generally shows more robust and consistent relations with dependence on various illicit substances than inattention which has only been associated with alcohol use ( Capusan et al, 2015 , Roberts et al, 2014 ).…”
mentioning
confidence: 99%
“…Our results showed differences between adult ADHD patients and the healthy group regarding their age and sex, but these differences were not significant after correcting with multiple statistical tests. Past studies have sometimes indicated a higher prevalence of young males in ADHD samples [41,42]. The younger age could be a result of the developmental nature of ADHD, which has its onset in childhood and can persist into adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Breda and colleagues [41] suggested that a biased recall of childhood symptoms, which are necessary to diagnose ADHD in adults, may affect the accuracy of the association with age. Moreover, the higher number of male ADHD patients is often associated with the greater externalization of symptoms among men [42].…”
Section: Discussionmentioning
confidence: 99%